2017
DOI: 10.3762/bjoc.13.282
|View full text |Cite
|
Sign up to set email alerts
|

Quinone-catalyzed oxidative deformylation: synthesis of imines from amino alcohols

Abstract: A new method for imine synthesis by way of quinone-catalyzed oxidative deformylation of 1,2-amino alcohols is reported. A wide range of readily accessible amino alcohols and primary amines can be reacted to provide N-protected imine products. The methodology presented provides a novel organocatalytic approach for imine synthesis and demonstrates the synthetic versatility of quinone-catalyzed oxidative C–C bond cleavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…We initially attempted Jones oxidation of β‐aminodiol 3 d following the same method as that used for compound 3 a ; however, as mentioned above, we confirmed that the reaction led only to decomposition of 3 d , and none of the target carboxylic acid 4 d was observed. Furthermore, careful examination of the reaction mixture disclosed formation of the corresponding benzophenone, probably through oxidative carbon−carbon cleavage in a similar fashion to that of 1,2‐aminoalcohols . This decomposition could not be suppressed when using metallic oxidants such as PDC, PCC, MnO 2 , and cat .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We initially attempted Jones oxidation of β‐aminodiol 3 d following the same method as that used for compound 3 a ; however, as mentioned above, we confirmed that the reaction led only to decomposition of 3 d , and none of the target carboxylic acid 4 d was observed. Furthermore, careful examination of the reaction mixture disclosed formation of the corresponding benzophenone, probably through oxidative carbon−carbon cleavage in a similar fashion to that of 1,2‐aminoalcohols . This decomposition could not be suppressed when using metallic oxidants such as PDC, PCC, MnO 2 , and cat .…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, careful examination of the reaction mixture disclosed formation of the corresponding benzophenone, probably through oxidative carbonÀ carbon cleavage in a similar fashion to that of 1,2aminoalcohols. [32][33][34] This decomposition could not be suppressed when using metallic oxidants such as PDC, PCC, MnO 2 , and cat. RuCl 3 /NaIO 4 .…”
Section: Synthesis Of ββ-Diaryl β-Hydroxy-α-amino Acidsmentioning
confidence: 99%
“…In the subsequent step, 2-pyrrolyl aniline III could undergo a condensation reaction with the preformed HCHO, which was generated from DMSO at a high temperature under acidic conditions, 28 resulting in the formation of imine VII . 29 The intramolecular Michael addition with imine VI could lead to the production of VIII via re-aromatization of the intermediate VII . Furthermore, aerobic oxidation of VIII could produce product 3a .…”
mentioning
confidence: 99%
“…Our research group has developed several quinone-catalyzed or quinone-mediated transformations for the synthesis of amine derivatives. During the development of a stepwise umpolung approach for the α-allylation of benzylic amines with allylpalladium species, we observed that iminoquinones derived from 3-butenylamines underwent cyclization by intramolecular C–N bond formation, leading to pyrrole products in low yields (see the Supporting Information).…”
mentioning
confidence: 99%